Immune deficiency/dysregulation associated lymphoid proliferations, EBV+ in persons living with HIV - Johanna Cevallos; Carmen Lome-Maldonado; Leticia Quintanilla-Martínez; Ivonne Montes-Mojarro; Beda Islas-Muñoz; Ana F. Ramírez; Leslie Chavez-Galán; Lucero Ramón-Luing; Patricia Volkow (Permanyer, 2024)
Background: The 5th edition of the World Health Organization Classification of Hematolymphoid Tumors recently defined immune deficiency/dysregulation (IDD)-associated-lymphoid-proliferations in HIV settings, where information is scarce, often gone under or misdiagnosed. Objectives: To describe the clinical picture, histopathology, and outcomes of IDD-associated-lymphoidproliferations Epstein-Barr virus+ (EBV) in people living with HIV without organ transplantation, antiretroviral therapy (ART) treated. Materials and Methods: HIV+ patients diagnosed with IDD-associated-lymphoid-proliferations seen at an academic medical center in Mexico from 2016 to 2019 were included. Immunohistochemical studies, in situ hybridization, and polymerase chain reaction analysis for EBV and LMP1 gene deletions were performed and correlated with clinical data. Results: We included 27 patients, all men who have sex with men, median age 36 years (interquartile range [IQR] 22-54). The median baseline CD4+ T cells were 113/mL (IQR 89-243), the CD4+/CD8+ ratio was 0.15 (IQR: 0.09-0.22), and the HIV viral load was 184,280 copies/mL (IQR: 76,000-515,707). Twenty patients (74.07%) had IDD-associated-lymphoid-proliferations hyperplasia plasma cell type EBV+, 3 (11.1%) had hyperplasia mononucleosis-like type (IM-type), 1 patient (3.70%) had florid follicular hyperplasia, 3 (11.1%) IDD-associated-lymphoid-proliferations polymorphic type, and there were 22 cases (81.4%) of synchronic Kaposi Sarcoma. Two patients were diagnosed with Hodgkin lymphoma following a second positron emission tomography-computed tomography scan-guided biopsy. The median follow-up was 228 weeks (IQR 50-269); 6 patients died (22.2%) of causes unrelated to IDD-associated-lymphoid-proliferations related. Conclusion: IDD-associated-lymphoid-proliferations EBV+ occured in severely immunosuppressed HIV+ patients, a high percentage of whom had concomitant Kaposi sarcoma. The prognosis was good in patients treated only with ART.